Cutaneous manifestations in renal transplant recipients - Baghel, Nekram; Awasthi, Sankalp; Kumar, Sweta S. (International Journal of Research in Medical Sciences, 2017)
Background: Skin lesions both benign and malignant occur frequently in renal transplant recipients receiving long term immunosuppressive drugs. Aim was to study cutaneous manifestations in renal transplant recipients (RTRs). Methods: Thirty two patients with chronic kidney diseases who underwent renal transplant were included in the study. All of the patients were fully examined for cutaneous, hair, nail and mucosal changes. Diagnostic measures such as scraping and biopsy of the lesions was carried out, where necessary. Results: Out of 32 patients, 23 (71.8%) were male and 9 (28.1%) were females. Skin infections occurred in 84.3% of the patients and most of them were fungal infections (37.5%), followed by viral infection in (31.2%) patients. Oral mucosal changes, hair and nail comprising of (34.3%), (71.8%), (43.7%) patients respectively. Only malignancy seen in one patient was basal cell carcinoma. Drug induced cutaneous manifestations were acneiform eruptions (18.75%), hirsutism (15.6%), hypertrichosis (9.3%), striae (6.25%), gingival hyperplasia (3.12%) and skin atrophy (3.12%). Conclusions: Skin lesions are a significant problem in renal transplant recipients. A careful monitoring of these patients is recommended for early diagnosis and treatment.